Complex (multispecies) livestock keeping: Highland agricultural strategy in the northern Horn of Africa during the Pre-Aksumite (1600 BCE–400 BCE) and Aksumite (400 BCE–CE 800) periods - Woldekiros, Helina S.; D’Andrea, A. Catherine (Frontiers in Ecology and Evolution, 2022)
The earliest settlements and states in the Horn of Africa were founded in mid to high-altitude areas by farmers and herders who were pioneers in agriculture and herding. Even today, places between mid- and high-altitudes remain densely populated. The ancient Pre-Aksumites and Aksumites (>800 BCE-900 CE) of the north Ethiopian and Eritrean highlands established one of the most powerful states in the Horn of Africa in these high altitude areas through control of long-distance trade and intensive and extensive agriculture. However, despite the fact that agriculture was a significant source of wealth and subsistence for these ancient polities, there has been little research into the agricultural strategies of Pre-Aksumite and Aksumite societies. Using archaeological and faunal data collected from the site of Mezber dating from 1600 BCE to 400 CE, as well as prevsiously published data, this article provides the oldest date as well as zooarchaeological evidence for the earliest farming practices in the Horn of Africa. The research demonstrates a resilient highland agricultural strategy based on multispecies animal and plant resources, similar to most tropical agricultural systems today. A second important strategy of the Pre-Aksumite farmers was the incorporation of both indigenous and exogenous plants and animals. In addition to one of the earliest dates and evidence for multispecies farming practice in highland Ethiopia, the Mezber site also offers one of the most thorough collections of such data available.